'Playing' at the ethnic boundary: strategic boundary making/unmaking among ethnic Chinese groups in Australia. Issue 4 (15th March 2016) - Li, Yao-Tai
ABSTRACT: The sociological literature has constructed a systematic typology of 'modes' and 'means' of strategic ethnic boundary making/unmaking. Through exploring different strategies, scholars illustrate the processes and contexts of boundary expansion or contraction. Other scholars also distinguish ethnic elements and 'moral' values attached to certain ethnicities but not to others. This paper acknowledges dynamic boundary making/unmaking and moral aspects of ethnicity, while exploring the different degrees to which national and pan-national identity nest within each other among ethnic Chinese groups, as well as how ethnic boundary becomes a field where people 'play' in their everyday interactions. Based on participant observations and in-depth interviews from two pan-Chinese worksites in Australia, the paper argues that different interpretations of ethnic identity as well as how different identities (national and pan-national) are nested give people room to 'play' at the ethnic boundary and result in different outcomes. This paper also shows that people can cross the ethnic boundary (between Taiwanese/Hong Kongese and PRC-Chinese) without expanding/contracting the existing categories or 'repositioning/transvaluing' their ethnic statuses.